SISTEM PENDUKUNG KEPUTUSAN SELEKSI SUPPLIER DENGAN PENDEKATAN METODE FIS MAMDANI PADA KOPERASI XYZ - puput irfansyah; Imam Sunoto (Faktor Exacta, 2015)
XYZ Cooperative is a cooperative engaged in trading and distributing. At this time the Cooperative XYZ act as distribution equipment medical equipment that also distribute other products such as medicinal products. As a cooperative distributors who deal directly with suppliers and customers that want to satisfy customer-oriented, and the many suppliers who want to distribute their goods through the Cooperative XYZ, then the cooperative is required to select suppliers which can be selected to establish good cooperation and benefit, is one aspect important that ensures the smooth operation of firms, and not disappoint the customer. Decision-making can be influenced by several aspects, this can affect the speed in taking decisions by the decision maker in which decisions must be fast and accurate. Rapid technological advances that increasingly make the decision-making process also requires information technology, this is due to globalization, which demands a cooperative to move quickly in taking a decision. Here, the role of decision support systems to take proper supplier selection decisions. Determination of supplier selection criteria are then processed with a fuzzy logic approach infrence mamdani system, so it can be obtained easily ranks suppliers to then be proposed as appropriate supplier. Results from this study are expected cooperative is able to determine the selection of suppliers in efekif, efficient, and objective. Keywords: Fis mamdani, criteria, selection, suppliers